Density and ice layer stratigraphy in 24 shallow firn cores from Southwest Greenland, 2017 - 2019 - Asa Rennermalm; Regine Hock; Federico Covi; Jing Xiao; Giovanni Corti; Sasha Leidman; Clement Miege; Jonathan Kingslake; Michael MacFerrin; Marco Tedesco (Arctic Data Center, 2021)
Observations of near-surface firn density and ice layer stratigraphy collected on the Greenland ice sheet are rare. This dataset contains information about twenty-four shallow firn cores drilled in the percolation zone in southwest Greenland between 2017 and 2019. Seven cores ranged between 2.9 and 6.3 meter (m) depth, with the remaining seventeen cores extending to 10–27 m depths. Each core has data on density, ice layer stratigraphy, and type of material (i.e. snow, firn, or ice). Quality control was performed on all data to replace erroneous data. More details including uncertainty analysis are provided in the method section and in Rennermalm et. al., (2021). The dataset includes the following files Core_meta_data.csv : File with metadata about each core, including location, site name, retrieval date, investigators, and other information Explanation_of_core_variables.csv : File with explanation of the variables reported in the core data files Core data files: For each core two files are included: a) a file with all field data with the following file naming convention [Site]-[Year]-[Core number], and b) a file only including the depth/thickness of all ice layers [Site]-[Year]-[Core number]_icelayer_data. Text in brackets are variables. References: Rennermalm, Å. K., Hock, R., Covi, F., Xiao, J., Corti, G., Kingslake, J., Leidman S. L., Miege, C., MacFerrin, M., Machguth, H., Osterberg, E., Kameda, T., McConnell. J. 2021. Shallow firn cores 1989 - 2019 in southwest Greenland’s percolation zone reveal decreasing density and ice layer volume after 2012. Journal of Glaciology, 1-12, https://doi.org/10.1017/jog.2021.102